Indicators of sarcopenia: Sex differences in competitive runners prior to peak muscle mass - Shoepe, T. C.; McCormack, W. P.; LaBrie, J. W.; Mello, G. T.; Almstedt, H. C. (International Journal of Sports Medicine, 2020)
Strength, muscle mass, and muscle quality have been observed to be compromised in low body-mass index individuals such as competitive runners, increasing their risk for sarcopenia. The purpose was to compare indices of sarcopenia in young runners to age, height, body-mass, and body-mass index-matched non-runners. Handgrip strength and arm composition from dual-energy x-ray absorptiometry (baseline-T1, T2=5.3±1.4, T3=11.5±0.7 months later) were assessed in 40 non-runners and 40 runners (19.3±0.7 vs. 19.2±1.1 years, 170.7±10.3 vs. 171.1±9.1 cm, 60.2±7.4 vs. 60.2±7.9 kg, 20.6±0.9 vs. 20.5±1.5 kg m-2). The unitless variable of muscle quality, was defined as the sum of right and left maximal handgrip (in kg) divided by the sum of bone-free lean mass of both arms (in kg). Female runners displayed the highest muscle quality (T1=15.3±1.7; T3=15.7±2.0) compared to male runners (T1=13.7±1.4, p < 0.001; T3=14.2±1.6, p < 0.001) and male non-runners (T1=12.4±1.8, p=0.001; T3=13.2±1.6, p < 0.001), while female non-runners (T1=14.6±2.5, p=0.154; T3=15.1 ±2.2, p=0.124) showed higher muscle quality than male non-runners. Higher muscle quality in low-body-mass index females persists over one-year during young-adulthood and while running contributes to whole-body muscle mass accrual, it does not appear to be significantly associated with improvements in the most commonly used upper-body diagnostic indicator of sarcopenia.